Pengaruh Promosi, Persepsi Harga dan Lokasi terhadap Keputusan Menginap di Wyndham Casablanca Jakarta - Dewi Ruth Angela Patty; Bambang Noer Supriyono (Human Capital Development, 2022)
The purpose of this study was to determine and analyze the effect of promotion, price perception, and location on the decision to stay at Wyndham Casablanca Jakarta. The population in this study are customers of Wyndham Casablanca Jakarta. Data were taken using accidental sampling as many as 120 respondents. In addition, 20 respondents for testing the validity and reliability, and 100 respondents for research calculations. The analytical method used in this study is the classical assumption test using SPSS version 20. From the measurement results with this method, the independent variables, which is promotion, price perception and promotion have a good and significant effect on the decision to stay at Wyndham Casablanca Jakarta.